2022
DOI: 10.1177/15346501221092112
|View full text |Cite
|
Sign up to set email alerts
|

Using Behavior-Analytic Treatment to Teach Tongue Lateralization Skills to Children With Avoidant/Restrictive Food Intake Disorder

Abstract: Oral-motor skills needed for efficient consumption of table-textured foods (e.g., tongue lateralization) often develop as children are exposed to food at increasingly higher textures (e.g., soft meltable, crunchy, and chewy; Volkert et al., 2014). For children with avoidant/restrictive food intake disorder (ARFID; American Psychiatric Association, 2013; World Health Organization, 2019), these oral-motor skills may not develop without intervention. We review case studies of three children diagnosed with ARFID w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…as providing attention for a desired behavior and not giving attention for undesirable eating and mealtime behaviors. Several studies involved escape extinction, in which the patient is not allowed to "escape" the feeding demand through re-presenting the food or not removing a spoonful of food (e.g.,McMahon et al, 2022;Phipps et al, 2022;Sharp et al, 2016). Working closely with parents was central to behavioral interventions, including didactic instruction, in vivo therapist feedback, modeling, and role-play with parents (e.g.,Bloomfield et al, 2019;Taylor et al, 2019).…”
mentioning
confidence: 99%
“…as providing attention for a desired behavior and not giving attention for undesirable eating and mealtime behaviors. Several studies involved escape extinction, in which the patient is not allowed to "escape" the feeding demand through re-presenting the food or not removing a spoonful of food (e.g.,McMahon et al, 2022;Phipps et al, 2022;Sharp et al, 2016). Working closely with parents was central to behavioral interventions, including didactic instruction, in vivo therapist feedback, modeling, and role-play with parents (e.g.,Bloomfield et al, 2019;Taylor et al, 2019).…”
mentioning
confidence: 99%
“…Differential reinforcement was also common, such as providing attention for a desired behavior and not giving attention for undesirable eating and mealtime behaviors. Several studies involved escape extinction, in which the patient is not allowed to “escape” the feeding demand through re‐presenting the food or not removing a spoonful of food (e.g., McMahon et al, 2022; Phipps et al, 2022; Sharp et al, 2016). Working closely with parents was central to behavioral interventions, including didactic instruction, in vivo therapist feedback, modeling, and role‐play with parents (e.g., Bloomfield et al, 2019; Taylor et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…This finding is problematic as existing research indicates that a lack of appropriate early experience with high-texture foods contributes to delays in the development of chewing, thus, emphasizing the critical role of practice in the development of rotary chewing ( Beckett et al, 2002 ). Similarly, Phipps et al (2022) also advocated for practice with increasingly higher texture foods in order to develop the basic skills necessary to consume regular texture foods.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they reported that adaptation of jaw control to different food consistencies was an important component in the development of rotary chewing. Phipps et al (2022) suggested that the components involved with chewing develop only when children are exposed to higher texture foods.…”
mentioning
confidence: 99%
See 1 more Smart Citation